(untitled) (World Bulletin of Management and Law, 2022)
As a result of the globalization of the world community, the rights and obligations of economic entities are guaranteed to be regulated by international treaties, conventions, as well as conflict of law rules that exist in national legislation. Today, the provision of modern technological tools and the rapid development of program activities are on the agenda for research to address the issue related to the rights of participants in these relations. In turn, it is important to take into account the laws and regulations of developed countries that have advanced in the field of digital financial services aimed at regulating this area. This article discusses the issues of alienation of digital financial assets as objects of civil legal relations, going beyond the generally accepted traditional approaches